Upgrading Crude Bio-Oil (CBO) Dari Biomassa Menjadi Upgrade Bio-Oil (UBO) Dengan Katalis Ni/Lempung - Subangkit Julio Jaya; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Objective of this research is to upgrade quality of bio-oil product from biomass of acacia. In this study several parameters were determined such us determine the effect of temperature reaction and ethanol : bio-oil ratio. And then compared physical and chemical characteristic of crude bio-oil (CBO) to upgraded bio-oil (UBO). In upgrading process, mixture of bio-oil and ethanol 36 gram, Ni/clay catalyst 0,3 gram, with variation of ethanol : bio-oil ratio are 5:1 (30 gram ethanol : 6 gram bio-oil), 3:1 (27:9) , 2:1 (24:12) and 1:1 (18:18) as well as temperature reaction variations are 60, 70 and 80 oC. The highest result on bio-oil yields 1:1 ratio and 60 oC was away 79,25% with calorific value increase from 3,784 into 18,339 MJ/kg. The dominant chemical components in crude bio-oil (CBO) such us aldehydes (58,91%), acids (13,43%) and esthers (12,26%) while in upgraded bio-oil (UBO) such us aldehydes (27,45%), phenols and furans (22,75%), alkanes and alkenes (19,48%), esthers (14,84%) and acids (1,53%) respectively. Keywords: bio-oil, upgrading bio-oil, crude bio-oil (CBO), upgraded bio-oil (UBO)